2015
DOI: 10.1039/c5ra08488a
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-derived ammonium salts as highly efficient catalysts for chemical fixation of carbon dioxide into cyclic carbonates under solvent-free conditions

Abstract: Ammonium salts based on nicotine proved to be highly efficient and recyclable catalysts for the synthesis of cyclic carbonates from epoxides and CO2 without the utilization of any organic solvent and any additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In contrast, non-nucleophilic anions such as NTf 2 − , PF 6 − or BF 4 − caused the loss of the catalytical activity of the studied BuDABCO salts. Interestingly, some of the attempts to boost the catalytic activity of onium salts constructing di-or tricationic ILs (Scheme 7) often fall flat (Figure 7) [66][67][68]. Surprisingly, when ILs containing activated CO 2 in their structures in N,N -di(alkyl)imidazolium-2-carboxylates were tested as CO 2 cycloaddition catalysts by Kayaki et al [65], the observed activity was quite low and a high CO 2 pressure was required to obtain satisfactory conversion (Table 13).…”
Section: Onium Salts As Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, non-nucleophilic anions such as NTf 2 − , PF 6 − or BF 4 − caused the loss of the catalytical activity of the studied BuDABCO salts. Interestingly, some of the attempts to boost the catalytic activity of onium salts constructing di-or tricationic ILs (Scheme 7) often fall flat (Figure 7) [66][67][68]. Surprisingly, when ILs containing activated CO 2 in their structures in N,N -di(alkyl)imidazolium-2-carboxylates were tested as CO 2 cycloaddition catalysts by Kayaki et al [65], the observed activity was quite low and a high CO 2 pressure was required to obtain satisfactory conversion (Table 13).…”
Section: Onium Salts As Catalystsmentioning
confidence: 99%
“…The hydrogen in position 2 on the imidazolium ring is, in all probability, important as an HBD for epoxide ring activation and substitution with -COO − causes a decrease in catalytic activity (Table 13). Interestingly, some of the attempts to boost the catalytic activity of onium salts constructing di-or tricationic ILs (Scheme 7) often fall flat (Figure 7) [66][67][68]. Interestingly, some of the attempts to boost the catalytic activity of onium salts constructing di-or tricationic ILs (Scheme 7) often fall flat (Figure 7) [66][67][68].…”
Section: Onium Salts As Catalystsmentioning
confidence: 99%
“…[40][41][42] We have also reported the investigation of a series of nicotinebased ammonium salts as catalysts for chemical fixation of carbon dioxide into cyclic carbonates, and it was found that monobenzylnicotinium bromide showed a much higher activity than dibenzylnicotinium bromide. [43] In continuation of our recent studies on the development of eco-friendly catalytic protocols, [44,45] herein, we report the synthesis and characterization of a nicotine-functionalized silica supported Pd complex as a recyclable solid catalyst. This new catalyst system having a synergistic effect of coordination and electrostatic interactions was found to be efficient in palladium-catalyzed C-C bond formation.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, we have used benzyl nicotinium chloride as the promoter in metal‐catalyzed C‐C and C‐S coupling reactions . We have also reported the investigation of a series of nicotine‐based ammonium salts as catalysts for chemical fixation of carbon dioxide into cyclic carbonates, and it was found that monobenzylnicotinium bromide showed a much higher activity than dibenzylnicotinium bromide …”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of biomass‐based protic ILs is usually achieved by pretreating or processing the respective biomass to yield primary, secondary, or tertiary amines, protonating them by strong acids, and exchanging the anion by metathesis reactions to the desired counterion . Similarly, by using quaternization reactions instead of strong acid treatment with the other reaction steps being the same, biomass‐based aprotic ionic liquids are available …”
Section: Electrolytes and Separatorsmentioning
confidence: 99%